Isolation, characterization, and transcription of the gene encoding mouse mast cell protease 7. - McNeil, H P (1992)
A gene that encodes mouse mast cell protease (mMCP) 7 (also known as mouse mast cell tryptase 2) was isolated by genomic cloning with a cDNA that encodes mMCP-6, a tryptase in serosal mast cells. cDNAs encoding mMCP-7 were isolated from a bone-marrow-derived mast cell cDNA library. The mMCP-7 gene spans 2.3 kilobases and contains five exons rather than six, as found in the mMCP-6 and human mast cell tryptase I genes. Comparison of the 5' end of the transcript with the genomic sequence indicated that the region corresponding to the first intron in the mMCP-6 and human tryptase I genes is not spliced during transcription of mMCP-7 mRNA because of a point mutation at the intron 1 acceptor splice site; this results in a 5' untranslated region of 195 nucleotides, which is longer than that of any other known mast cell-specific transcript. mMCP-7 is 71-76% homologous with mMCP-6 and with dog and human mast cell tryptases, and it is the most acidic mast cell protease, with an overall net charge of -10. RNA blot analyses revealed that the mMCP-7 gene is transcribed in bone-marrow-derived mast cells but is not transcribed in mature serosal mast cells or in mucosal mast cell-enriched intestinal tissue of Trichinella spiralis-infected mice. Transcription of the mMCP-7 gene by differentiating bone-marrow-derived mast cells occurred within 1 week of bone-marrow culture but decreased dramatically after 3 weeks. Thus, the mMCP-7 gene displays a number of unusual structural characteristics and is distinctive in its transient and selective expression in immature mast cells maintained in interleukin 3-enriched medium.